Microbiologically Influenced Corrosion in Floating Productions Systems - Machuca Suarez, Laura; Polomka, Anthony (2018)
Microbiologically influenced corrosion (MIC) represents a serious and challenging problem in Floating, Production, Storage and Offloading vessels (FPSOs), one of the most common type of offshore oil production facilities in Australia. Microorganisms can attach to metal surfaces, which under certain conditions, can result in corrosion rates in excess of 10 mm per year (mmpy) leading to equipment failure before their expected lifetime. Particularly, increasing water cut (ratio of water vs. total fluids produced), normally resulting from the age of the assets, results in an increased risk of MIC. This paper provides an overview of causative microorganisms, their source of contamination and the areas within FPSOs that are most prone to MIC. Although mitigation practices such as chemical treatments, flushing and draining and even cathodic protection are effective, MIC can still occur if the systems are not properly monitored and managed. A case study is presented that describes the microorganisms identified in a FPSO operating in Australia suspected of having MIC issues.